DEMOCRATIC TRANSITION AND REFLECTION ON INDONESIA'S EFFORTS TO ENCOURAGE DEMOCRATIZATION IN MYANMAR - Chandra Purnama; Windy Dermawan; Emil Mahyudin (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This paper aims to analyze the motives and forms of Indonesia’s effort towards Myanmar in promoting democratization. To achieve these objectives, described the historical aspects of Indonesia-Myanmar relations, democratic transition in both countries, and other forms of Indonesian support for Myanmar in encouraging democratization. Qualitative methods is used in this study to collect and analyze data from interviews and literature studies. Based on this research, found that Indonesia's support for Myanmar in encouraging democratization was influenced by the historical aspects of bilateral relations between Indonesia and Myanmar, the success of Indonesia's transition to democracy, and the similarities of socio-cultural characteristics in both countries. Indonesia's foreign policy towards Myanmar in supporting democratization is done bilaterally, regionally within ASEAN, and multilaterally within UN forums. The principle of active and independent foreign policy and ASEAN norms become the guidance for Indonesia in supporting democratization of Myanmar.